Synthesis, Spectral Characterization and Antimicrobial Activity of Some Transition Metal Complexes of 1,3-Bis(1H-benzimidazol-2-yl)-2-oxapropane - YALÇIN, BAHATTİN (WILEY-V C H VERLAG GMBH, 2014)
1,3-Bis(1H-benzimidazol-2-yl)-2-oxapropane (L) complexes with Fe(NO3)(3), CoCl2, Co(NO3)(2), Ni(NO3)(2), CuCl2, Cu(ClO4)(2), PdCl2, CdI2, Hg(NO3)(2) were synthesized and characterized by elemental analysis, molar conductivity, magnetic moment, TGA, FT-IR, NMR, ESI-MS, fluorescence spectroscopy. Also, the crystal structure of 1,3-bis(1H-benzimidazol-2-yl)-2- oxapropane] dichlorocobalt(II), [Co(L)Cl-2], complex is reported that it has distorted trigonal bipyramidal geometry. Antibacterial activities of the compounds were evaluated using the disk diffusion method against six bacteria and Candida albicans. The Hg(II) complex shows superior activity toward S. epidermidis and E. coli whereas the other complexes are ineffective except the Co(NO3)(2) complex: it showed weak activity toward all of the microorganisms.
Keywords: Bis-benzimidazole; Oxapropane; Metal complexes; Antimicrobial; Crystal structure; COPPER(II) COMPLEXES; CRYSTAL-STRUCTURE; STRUCTURAL-CHARACTERIZATION; HG(II) COMPLEXES; MAGNETIC-PROPERTIES; BIS-BENZIMIDAZOLES; CU(II) COMPLEXES; DNA-BINDING; ZN(II); LIGAND